The Profile of Affective Abilities at Elementary School Students in Natural Science Learning Based on Learning Styles - Deva Fitria Wardhani; Septi Budi Sartika (Journal of Innovation in Educational and Cultural Research, 2024)
The background of this research is the importance of knowing the profile of students’ affective ability during learning so that the teaching and learning process can be successful. This study aims to describe the profile of the affective abilities of elementary school students in natural science learning in terms of their learning styles. This research uses a qualitative approach with a phenomenological type, with data collection techniques through observation and interviews. The subjects in this study were six students, namely two students with a visual learning style, two with an auditory learning style, and two with a kinesthetic learning style. The result showed that 1) The profile of affective ability of students with visual learning style is two indicators of affective ability, namely indicators of receiving and appreciating, 2) The profile of students’ affective ability with auditory learning styles is three indicators of abilities, namely indicators of receiving, responding and organizing, 3) The profile of affective ability of students with kinesthetic learning style is that no affective ability indicators are met. The conclusion of this research is to know the profile of the affective ability of elementary school students in science learning in terms of different learning styles.